COMPARATIVE STUDY OF CONSUMER PREFERENCE BETWEEN KOPI KENANGAN AND BLACK CUP COFFEE CUSTOMERS - Andrea Kalesaran; Paulus Kindangen; Merinda H. C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The presence of coffee house modern or coffee shop has given a change of culture in Indonesia, where it is no longer only a big fan of coffee who wants to go to a coffee shop because nowadays it is not only to fulfill the functional needs, but it leads to emotional needs. It became the part of modern lifestyle where some people need to consume coffee before they do their own activity. Consequently, coffee consumption in Indonesia continues to increase, and it also increase consumer demand for Coffee business. The aim of this research is to analyze consumer preferences of coffee shop between Kopi Kenagan and Black Cup Coffee in Manado measure by brand image, brand loyalty, perveived price and electronic word of mouth. This research is quantitative type of research, which uses primary data obtained through questionnaires and uses independent sample t-test as the analytical tool. The population of this research is peoples in Manado who has experience in Kopi Kenagan and Black Cup Coffee, where the sample size is taken from 130 respondents who also has experience with both stores. The result from this research found that there is no significant difference between Kopi Kenagan and Black Cup Coffee measured by brand image, brand loyalty, perceived price and electronic word of mouth. Kopi Kenagan and Black Cup Coffee should more considering and be more focus on these factors that influence the consumer buying behavior.   Keywords: brand image, brand loyalty, perceived price, e-wom, consumer preferences, coffee shop